The Effect of Preconception Paternal Alcohol Exposure on Epigenetic Remodeling of the H19 and Rasgrf1 Imprinting Control Regions in Mouse Offspring - Knezovich, Jaysen G.; Ramsay, Michele (Frontiers in Genetics, 2012)
Imprinted loci play a critical role in fetal development. Their expression is often regulated by CTCF protein binding at imprinting control regions (ICRs). Parental alcohol exposure has been shown to reduce global DNA methylation in the developing mouse fetus. This study explored the effect of preconception paternal alcohol exposure on DNA methylation at two paternally methylated ICRs (H19 and Rasgrf1) in the sperm of exposed males and somatic DNA of sired offspring. Significant reductions at the H19 CTCF 1 (p=0.0027) and CTCF 2 (p=0.0009) binding sites were observed in the offspring of ethanol-treated sires, which was significantly correlated with reduced weight at postnatal days 35 to 42 (p<0.05). As birth weight was unaffected and growth was only delayed during the postnatal weaning period, with subsequent re-convergence, we hypothesise that this may be the result of a mental deficit causing delayed establishment of independent feeding following weaning and would explain why this effect is transient. No difference in DNA methylation was observed in the sperm of alcohol-exposed males, indicating that the transmission of the epigenetic signal at conception is not due to altered methylation, but may be the result of an RNA-mediated mechanism or altered chromatin remodelling.